Unleashing Central America’s Growth Potential : Honduras - Ulku, Hulya (World Bank, Washington, DC, 2021)
Despite advances in the growth reform agenda in the last decade, Honduras remains the second-poorest country in Central America, with one of the lowest growth rates in income per capita. The objective of this study is to investigate the drivers and constraints of growth and productivity in Honduras and explore areas with high growth potential. The value added of this study is to provide an in-depth analysis of the drivers and constraints of Honduras’s growth using a wide range of analytical tools. According to the growth diagnostics methodology, this report finds that the areas preventing faster growth are: (i) corruption; (ii) security; (iii) property rights; (iv) innovative activities; and (v) access of small firms to finance. Tackling the identified growth constraints can help Honduras in the transition from an exporter of low-complexity products to an economy with higher share complex products. This report has identified several key areas in which Honduras lags its comparator and aspirational countries, but which can help boost productivity and growth over the medium to long term. They include: improving transparency, accountability, and rule of law; reducing crime and violence; creating an enabling environment for innovation; improving the rule of law to better protect property rights and reduce expropriation risk; increasing the access of finance to small firms; and coordinating with the private sector to identify missing public goods and design mechanism to provide them.